The organization of shape and color in Vision and Art - Pinna, Baingio (Frontiers in Human Neuroscience, 2011)
The aim of this work is to study the phenomenal organization of shape and color in vision and art in terms of microgenesis of the object perception and creation. The idea of ‘microgenesis’ is that the object perception and creation takes time to develop. Our hypothesis is that the roles of shape and color are extracted in sequential order and in the same order these roles are also used by artists to paint objects. Boundary contours are coded before color contours. The microgenesis of the object formation was demonstrated (i) by introducing new conditions derived from the watercolor illusion, where the juxtaposed contours are displaced horizontally or vertically, and based on variations of Matisse’s Woman, (ii) by studying descriptions and replications of visual objects in adults and children of different ages, and (iii) by analyzing the linguistic sequence and organization in a free naming task of the attributes related to shape and color. The results supported the idea of the microgenesis of the object perception, namely the temporal order in the formation of the roles of the object properties (shape before color). Some general principles were extracted from the experimental results. They can be a starting point to explore a new domain focused on the microgenesis of shape and color within the more general problem of object organization, where integrated and multidisciplinary studies based on art and vision science can be very useful.